The evaluation of lymphatic vessel density and microvessel density in laryngeal squamous cell carcinoma - Ganime Çoban (Archives of Clinical and Experimental Medicine, 2018)
Aim: Metastasis to the cervical lymph nodes in laryngeal carcinomas is a factor reducing survival significantly.  The present study aimed to reveal the association of lymph node metastasis with lymphatic vessel density and microvessel density in the intratumoral and extra-tumoral areas of laryngeal squamous cell carcinoma.Methods: Eighty-six cases diagnosed with laryngeal squamous cell carcinoma in Pathology Department of Erciyes University Faculty of Medicine between 2000-2006 were included in the present study. Lymphatic vessel density and microvessel density were assessed with D2-40 which is an immunohistochemical marker in intratumoral and extra-tumoral areas and CD34, respectively. The results were compared with tumor grade, tumor localization, and lymph node metastasis. Results: Intratumoral and extra tumoral lymphatic vessel density value were 8.93±12.5 and 24.1±20.1, respectively (p=0.001). Mean intra tumoral microvessel density was calculated as 217.53±89.8 while extra tumoral microvessel density was calculated as 330.43±92.4 (p=0.001). Intratumoral lymphatic vessel density value was higher in the well-differentiated tumors compared to the poorly differentiated tumors but no significant result was obtained (p=0.100). Extra tumoral microvessel density value was found to be significantly higher in the poorly differentiated tumors (p=0.05). Intratumoral microvessel density value was significantly lower in tumors with lymph node metastasis (p=0.028). Extra-tumoral lymphatic vessel density value was higher in both groups with and without lymph node metastasis, however, no statistically significant result could be obtained (p=0.084). Conclusion: In the present study, intratumoral microvessel density was higher in well differentiated tumors whereas extra tumoral microvessel density was determined to be higher in poorly differentiated cases. No significant association was noted between lymphatic vessel density and differentiation. Extra tumoral and intra tumoral microvessel density values were found to be higher in the group without metastasis.  No association was detected between metastasis and lymphatic vessel density value.